Diasporic Literary Influence on World Literature (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The article reflects the most critical facts about Diaspora Literature. It also analyses the central concept of ‘Diaspora’. The main concern focuses on Afghan-American literature, its evaluation and its representatives.